FORMULASI LILIN AROMATERAPI MINYAK ATSIRI DAUN KEMANGI SEBAGAI ANTISTRESS - Erni Murniningsih; Eka Trisnawati; Mila Ulfaturro’iqoh (Parapemikir : Jurnal Ilmiah Farmasi, 2022)
Stress is a condition of the reality of life from life changes that cannot be avoided. Prolonged exposure to stress causes a decrease in the immune system. Stress prevention using natural aromatherapy needs to be researched. Basil (Ocimum basilicum) is one of the plants that can be used for aromatherapy because it is rich in essential oils. Candles are easily able to vaporize the compounds they contain. This study aims to formulate aromatherapy candles of basil essential oil as an antistress. The method of detecting antistress is the forced swim test with a Post-test control group design approach. Data were analyzed using ANOVA. Candles are made with essential oil concentrations (K: 0%; F1:2%, F2:4%, and F3:6%). It produces white wax and has a distinctive aroma of essential oils that meets SNI standards. Candles F2 and F3 are the best formulas as antistress compared to K and F1 with a Sig value. 0.00 (0.05).